2006
DOI: 10.1002/jbm.a.30786
|View full text |Cite
|
Sign up to set email alerts
|

Substrate mineralization stimulates focal adhesion contact redistribution and cell motility of bone marrow stromal cells

Abstract: Understanding the mechanisms of substrate based control of cell function is critical to the design of biomaterials. Cells interact with their extracellular matrix through cell adhesion contacts. We have previously described the self assembly of bone-like mineral onto an organic template and have shown that these biomimetic surfaces lead to an increased volume fraction of bone regenerated in vivo. In the present study, we compared the distribution of cell adhesion contacts, cell spreading, and cell motility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Cells directly interact with their surrounding matrix via focal adhesions [33,47,56] and cells respond to mechanical cues such as substrate stiffness via these focal adhesions. Leonova et al showed that the mineralisation of substrates stimulates focal adhesion and motility of MSCs [58]. It is suspected that the addition of nHa is resulting in the adherence of more cells than in the collagen alone and collagen-GAG scaffolds due to increased scope for focal adhesion because of the presence of nHa.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Cells directly interact with their surrounding matrix via focal adhesions [33,47,56] and cells respond to mechanical cues such as substrate stiffness via these focal adhesions. Leonova et al showed that the mineralisation of substrates stimulates focal adhesion and motility of MSCs [58]. It is suspected that the addition of nHa is resulting in the adherence of more cells than in the collagen alone and collagen-GAG scaffolds due to increased scope for focal adhesion because of the presence of nHa.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Bone marrow stromal cells were isolated from the long bones of 5-week-old C57BL/6 mice (University of Michigan UCUCA approval #08633), as described (24). BMSCs mixed with ␣-MEM (Gibco Laboratories) enriched with 10% FBS (Gibco Laboratories) and 100 g/mL penicillin G plus 100 IU/mL streptomycin were plated at 30,000 cells/cm 2 at 37°C in 5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…Inorganic components, such as hydroxyapatite, can improve protein adsorption and subsequent cell adhesion (Akkouch et al, 2011; Dimitrievska et al, 2008; Leonova et al, 2006; Li et al, 2009; Venugopal et al, 2010; Zhao et al, 2006a). Mineralized polymer surfaces can also be used to provide sustained release of growth factors and genes (Luong et al, 2006; Luong et al, 2009; Murphy et al, 2000; Segvich and Kohn, 2009).…”
Section: Cell Adhesion and Proliferation On Polymeric Materialsmentioning
confidence: 99%